"It's Hard to Talk When Your Child Has a Life Threatening Illness": A Qualitative Study of Couples Whose Child Is Diagnosed With Cancer. (November 2020) - Hooghe, An; Rosenblatt, Paul C.; Vercruysse, Trui; Cosyns, Veerle; Lambrecht, Karolien; Rober, Peter
When parents are confronted with something as fundamental as a cancer diagnosis for their child, it is generally assumed that sharing the emotional impact of it, in the form of talking about it with the partner, is helpful and necessary to cope as an individual and a couple. However, couple communication in the context of childhood oncology is often challenging. In this qualitative research, we aimed for a better understanding of how partners experience their couple communication during treatment of their child. Thematic coding was done on in-depth interviews with 16 parents (7 couples interviewed together and 2 mothers). We found that the circumstances of the treatment period affected couple communication. In the interviews, parents provided three main meanings to their limited talking: (a) because of the hospital and treatment context; (b) for self-care/self-protection related to the value of blocking emotions; and (c) because of each other. These findings invite us to rethink emotional closeness being equated with frequent or intense emotional communication in couples with a child who has cancer. This research, framed in a dialectic approach, emphasizes the value of both talking and not talking in the tense and challenging couple situation of dealing with a child's cancer diagnosis and treatment. Rather than advocating for the general promotion of open communication, our study suggests the value of hesitations to talk at certain points in the process, while also taking into account the degree of marital difficulties in offering interventions aimed at improving couple communication.